RESEARCH OF QUALITY OF COMMODITY MILK FROM FARMS OF DIFFERENT FORMS OF OWNERSHIP - Трофименко, Вита; Ковальчук, Татьяна; Дидух, Николай (SWorldJournal, 2020)
Dairy products are a key part of food life. Therefore, dairy products are an important product of the food industry. The market of milk and dairy products of Ukraine is very diverse and highly competitive. The basis of the dairy market in Ukraine are d